Relapse-specific genetic patterns in the exomic mutational landscape in acute myeloid leukemia - Wardah Qureshi; Aisha Jamal; Atia Gohar; Marium Imran Mansuri; Muhammad Irfan; Ishtiaq Ahmad Khan; Muhammad Shakeel (Egyptian Journal of Medical Human Genetics)
Abstract Background Acute myeloid leukemia (AML) is a blood malignancy that develops in the bone marrow due to uncontrolled cell proliferation and undifferentiating blood cells. This fast-progressing cancer has a higher percentage of relapses due to clonal evolution and the re-emergence of resistant clones. Identification of relapse associated genetic elements in AML remains a challenge. In this prospective study, whole-exome sequencing was performed in newly diagnosed cytogenetically normal AML. The patients treated with 7 + 3 induction or a hypomethylator were followed up until a response (remission, refractory, or relapse, etc.) was observed. The exome data was analyzed using the standard bioinformatics pipeline of GATK best practices and subsequent annotation and filtration with disease specific databases (ANNOVAR, ClinVar) to assess the impact of somatic as well as germline variants on the disease outcome. Results The AML who received 7 + 3 induction, 3 were on complete remission, 1 relapsed, while 3 were refractory to disease. Those receiving the hypomethylator regime, 3 went to remission, 2 persistence of the disease, and 1 relapsed after 6 cycles of chemotherapy. In genomic analysis, there were, on average, 32.21 rare germline and 5.64 rare somatic variants per patient. The tumor mutation burden (TMB) was significantly higher in the AML who relapsed (or refractory) compared with the remission AML (Wilcoxon rank sum p < 0.05). The mutational landscape indicated mutations in FER1L6, NRAP, DOCK10, MDN1, NBEAL2, and NCOR2 genes in relapsed AML only. Further, the COSMIC somatic signatures 8, 14, 25 were only observed in the relapse AML, whereas COSMIC somatic signatures 21, 23, 24, 30 were detected in the remission AML. Furthermore, the contribution of COSMIC signature 13 was significantly higher in the relapse AML compared with the remission AML (p < 0.05). Conclusion Collectively, this study determined genetic elements distinctive to relapsed AML. Although limited number of samples were sequenced, yet these findings can contribute to the prognostic assessment of cytogenetically normal AML.